The effect of different desalting methods on the quality of injected brine and pickle presalted bacalao from Atlantic Cod (Gadus morhua) - Mohammed Raheem Waheed Almozani 1977- (2021)
In the North Atlantic countries, salting and drying of cod and other fish species has been practiced for centuries. However, changes in consumer’s lifestyles have resulted in a decrease in salted cod consumption. Today, consumers demand ready-to-use, high-quality, nutritious food items, and the food industry must meet this demand. As a result, the possibility of adding an industrial desalting step to the national production should be investigated.Three different desalting treatments were used in this experiment for desalting of heavily salted Atlantic cod (Gadus morhua) loins, which were pre-salted either with brine injection or pickle salting. The tested desalting methods were i) desalting in still water (control), ii) desalting in water with circulation (movement), and iii) desalting in water with a continuous flow (flow). The effect of these different treatments on desalting yield, cooking yield, color, texture (compression and Warner-Bratzler test), salt content, water content, and desalting time were investigated. The highest desalting yield for the brine injected cod loins was obtained in the control treatment, while for the pickle salted cod it was obtained for the movement treatment (125% for both). The cooking yield % followed the same pattern (82%for both). Lightness values (L-values) tended to increase after desalting, and even further after cooking for all treatments. Redness values (a*-values) decreased after desalting and cooking, with more reduction after cooking for the brine injected samples. Yellowness values (b*-values) decreased after desalting for both brine injected and pickle salted loins, however the values tended to increase again after cooking. Compression tests indicated that the movement treatment had the highest hardness, while the flow treatments showed the softest texture for both desalted brine injected and pickle salted cod. The flow treatment showed higher hardness after desalting in both cod types during Warner-Bratzler testing, although the hardness was higher in the movement ...